Do People Understand Monetary Policy? - Carlos Carvalho; Fernando Nechio (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
We combine questions from the Michigan Survey about the future path of prices, interest rates, and unemployment to investigate whether households are aware of the basic features of U.S. monetary policy. Our Öndings support the view that at least some groups of households form their expectations about the future path of interest rates, ináation, and unemployment in a way that is consistent with those features. However, we also document a large degree of variation in the pattern of household responses over the business cycle. In particular, the negative relationship between unemployment and interest rates that is apparent in the data only shows up unequivocally in householdsíanswers during periods of labor market weakness.
Keywords: E52; E58; 330; survey data; monetary policy; communication; Taylor rule; inflation expectations; Michigan Survey; Survey of Professional Forecasters